simply (31/2+21/3)(32/3-31/3)21/3+22/3
Answers
Answered by
2
Step-by-step explanation:
Input Equation can be rewritten:
= (31/2+21/3)*(32/3-31/3)*21/3+22/3
= (15.5+21/3)*(32/3-31/3)*21/3+22/3
= (15.5+7)*(32/3-31/3)*21/3+22/3
= (22.5)*(32/3-31/3)*21/3+22/3
= 22.5*(32/3-31/3)*21/3+22/3
= 22.5*(10.666666666667-31/3)*21/3+22/3
= 22.5*(10.666666666667-10.333333333333)*21/3+22/3
= 22.5*(0.33333333333333)*21/3+22/3
= 22.5*0.33333333333333*21/3+22/3
= 7.5*21/3+22/3
= 157.5/3+22/3
= 52.5+22/3
= 52.5+7.3333333333333
= 59.833333333333
Similar questions